(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
Play has been long recognized as an essential aspect not only of childhood but also of human development. Some of the earliest studies in the related field started in the 1890s with G. Stanley Hall, founder of the child study movement that sparked a special interest in the developmental, mental and behavioral world of children. The American Academy of Pediatrics (AAP) published a comprehensive study in 2006 entitled: “The Importance of Play in Promoting Healthy Child Development and Maintaining Strong Parent-Child Bonds”. The above mentioned study states that “free and unstructured play is healthy and - in fact –essential helping children reach important social, emotional, and cognitive developmental milestones as well as helping them manage stress and become resilient.”